2017
DOI: 10.18632/oncotarget.15891
|View full text |Cite
|
Sign up to set email alerts
|

High Myc expression and transcription activity underlies intra-tumoral heterogeneity in triple-negative breast cancer

Abstract: We have previously identified a novel intra-tumoral dichotomy in triple-negative breast cancer (TNBC) based on the differential responsiveness to a reporter containing the Sox2 regulatory region-2 (SRR2), with reporter responsive (RR) cells being more stem-like than reporter unresponsive (RU) cells. Using bioinformatics, we profiled the protein-DNA binding motifs of SRR2 and identified Myc as one of the potential transcription factors driving SRR2 activity. In support of its role, Myc was found to be highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
(85 reference statements)
2
27
0
Order By: Relevance
“…It is well known that there is a higher proportion of MYC DNA amplification and mRNA high expression in TNBC compared to other subtypes [1,8]; however, the impact of MYC DNA amplification and mRNA high expression in TNBC is not fully understood. In our results, we found that MYC mRNA high expression, but not DNA amplification, in TNBCs was associated with worse OS, which is consistent with previous reports showing that high expression of MYC mRNA is associated with worse prognosis in TNBCs [5]. These findings further imply that MYC mRNA expression, but not DNA amplification, represents true activation of the oncogene.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well known that there is a higher proportion of MYC DNA amplification and mRNA high expression in TNBC compared to other subtypes [1,8]; however, the impact of MYC DNA amplification and mRNA high expression in TNBC is not fully understood. In our results, we found that MYC mRNA high expression, but not DNA amplification, in TNBCs was associated with worse OS, which is consistent with previous reports showing that high expression of MYC mRNA is associated with worse prognosis in TNBCs [5]. These findings further imply that MYC mRNA expression, but not DNA amplification, represents true activation of the oncogene.…”
Section: Discussionsupporting
confidence: 92%
“…MYC promotes oncogenesis by regulating cell growth and metabolism [4]. MYC is also associated with stem cell features such as chemo-resistance and self-renewal capability [5]. Thus, MYC transcription is strictly regulated by many signaling pathways including WNT/β -catenin, Notch, and TGF-β pathways [1].…”
Section: Introductionmentioning
confidence: 99%
“…For mammosphere assay, cells were seeded and cultured as previously described [ 11 ]. Briefly, cells were trypsinized and passed through a 40 μm cell strainer (BD, Franklin Lakes, NJ, USA) and seeded into ultra-low adherent plates (Corning, NY, USA) in Mammocult media (StemCell Technologies, Vancouver, BC, Canada) as per manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…MYC expression promotes BC proliferation and malignancy [ 4 , 16 , 17 ]. MYC–MAX–MAD network is important for regulating cell physiology [ 18 , 19 ]. This network includes transcriptional regulators that form different heterodimers that activate or repress target gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the proteins in this network function as a molecular switch to regulate gene expression. MYC together with its heterodimerisation partner MAX functions as a tumour-promoting transcriptional regulator [ 17 , 19 ]. In contrast, MAD1, a member of this network, functions as a transcriptional repressor and interacts with MAX to deactivate this molecular switch, thus antagonising the MYC–MAX complex that activates this molecular switch [ 20 ].…”
Section: Introductionmentioning
confidence: 99%